530 INTERPRETATION OF HBA1C VALUES IN GERIATRIC PATIENTS WITH TYPE 2 DIABETES: LARGE DIVERGENCE BETWEEN CLINICAL PRACTICE GUIDELINES. (14th June 2021) - Christiaens, A; Boland, B; Henrard, S
Abstract: Introduction: An individualised glycated haemoglobin (HbA1c) target according to the patients' health status is central in the glycaemic management of geriatric people with type 2 diabetes (T2D) in order to avoid hypoglycaemic events through an appropriate management of the glucose-lowering therapy (GLT). Current clinical practice guidelines (CPGs) provide different recommendations for patients' HbA1c targets. Using real-life data from geriatric patients, this study aimed at assessing the concordance in interpretation of HbA1c values according to three current major CPGs from the Diabetes Canada-2018 (DC18), the Endocrine Society-2019 (ES19) and the American Diabetes Association-2020 (ADA20). Introduction: Retrospective study in consecutive older patients (≥75 years) with T2D admitted to a Belgian geriatric ward, with GLT before admission and HbA1c measurement during the hospital stay. Patients were classified into three categories of HbA1c values according to the CPGs recommendations: in-target HbA1c (appropriate-GLT), too-low HbA1c (GLT-overtreatment) and too-high HbA1c (GLT-undertreatment). Concordance of health status classifications and GLT categories between the three CPGs was assessed using Cohen's and Fleiss' κ, respectively. Results: Of the 318 patients (median age 84 years, 54% women), one-third were in intermediate health and two-thirds in poor health (κ = 0.86; excellent concordance). According to the DC18, ES19 and ADA20 CPGs, HbA1c was in-target for respectively 46%, 25% and 82% of the patients, and too-low HbA1c (GLT-overtreatment) was present in 28%, 57% and 0% (κ = 0.36; low concordance). Results: Patients' HbA1c values are interpreted differently according to these major CPGs, mainly because of differences in their recommendations about HbA1c target individualisation and specifically the definition of a too-low HbA1c value. In clinical practice, these diverging interpretations regarding overtreatment may lead to unsafe GLT prescribing and thereby to hypoglycaemic events in this high-risk population.